Bird Shelters in Turkey: Birdhouses and Dovecotes - Ozen, Rahsan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2012)
The present paper was aimed at the description of bird shelters constructed in various regions of the Anatolian peninsula, and based on these findings, at the qualitative assessment of the human - animal bond throughout Turkish history. In Turkish societies, all which have valued animals greatly; birds have been creatures well-loved and believed to bring luck. In particular, birds, including sparrows, swallows, collared doves, pigeons and storks, have been considered to be sacred and have been valued dearly. In Turkish history, starting from the 13th century, special shelters were built for birds, sometimes to protect them from danger and sometimes to make use of them. These shelters may be classified under two titles, namely, birdhouses and dovecotes. Following the detailed assessment of several features of bird shelters, including their site and date of construction, and architecture, it was concluded that birdhouses and dovecotes were distinctive structures; the former designed from a zoocentric point of view and the latter an anthropocentric perspective, all which reflect the sociocultural features of the period in which they were built.
Türkiye'de kuş yuvaları: Kuşevleri ve güvercinevleri
Keywords: Bird shelters; Birdhouses; Dovecotes